The Relationship Between Emotional Intelligence and Clinical Success at the Completion of One Year of Courses for Diagnostic Medical Sonography or Radiography Students. - Miller, Elena (Journal of Diagnostic Medical Sonography, 2023)
Objective: Since most health care programs have competitive entry and selective admission procedures, it is essential for colleges to select proper admissions tools to ensure student success in the health care programs. The purpose of the study was to determine what relationship exists between emotional intelligence (EI) and clinical success for diagnostic medical sonography (DMS) or radiography (RT) students. The main goal of this work was to explore if an EI model such as the Trait Emotional Intelligence Questionnaire (TEIQue) can be potentially used as one of the criteria in the admission selection process for DMS and RT programs in the future. Materials and Methods: The participants of this study were 26 imaging students. The convenient sample included 10 DMS and 16 RT students, enrolled in an Associate Degree in Applied Sciences program, within a community college. The study was conducted by administering the TEIQue questionnaire that collected EI data and demographic data of the participants in both programs. These data were gathered at the beginning of each respective program and 1 calendar year later. The clinical student success was examined over a period of 2 clinical semesters. Results: The analysis of the findings determined that a significant relationship existed between all EI variables such a global EI, 4 factors and 3 subscales of trait EI for both groups of students. The findings of this study did not show a significant relationship between clinical success and global EI as well as 3 subscales of trait EI for DMS or RT students. Nevertheless, a statistically significant increase was observed among 1 of the 4 EI factors, well-being, among RT students. Interestingly, DMS students did not show the same outcome. Conclusion: The results of this study provide limited empirical evidence that a strong relationship may exist between 1 of the 4 trait EI factors, well-being, among RT students and clinical success in this RT student cohort. This is an important finding that may support the use of the TEIQue questionnaire, as part of the admissions process for other RT programs. The DMS students did not exhibit the same results. However, the findings with the RT students demonstrate the need for further research.